Techniques for extraction of bioactive compounds from plant materials: a review - Azmir, Jannatul; Sarker, Md. Zaidul Islam; Rahman, Md. Mokhlesur; Khan, Sharif; A., Mohamed; Ferdosh, Sahena; M. H. A., Jahurul; K., Ghafoor; Nik Ab Rahman, Nik Norulaini; A. K. M., Omar (Elsiver, 2013)
The use of bioactive compounds in different commercial sectors such as pharmaceutical, food and chemical industries signifies the need of the most appropriate and standard method to extract these active components from plant materials. Along with conventional methods, numerous new methods have been established but till now no single method is regarded as standard for extracting bioactive compounds from plants. The efficiencies of conventional and non conventional extraction methods mostly depend on the critical input parameters; understanding the nature of plant matrix; chemistry of bioactive compounds and scientific expertise. This review is aimed to discuss different extraction techniques along with their basic mechanism for extracting bioactive compounds from medicinal plants